Leading the Web in Concurrent Engineering : Next Generation Concurrent Engineering - Ghodous, P. (Parisa); Dieng-Kuntz, Rose; Loureiro, Geilson (Frontiers in artificial intelligence and applications, 2006)
Contains papers on the advances in Concurrent Engineering research and applications. This book focuses on developing methodologies, techniques and tools based on Web technologies required to support the key objectives of Concurrent Engineering.